2013
DOI: 10.1016/j.foodchem.2012.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of fractions, essential oil, carnosol and betulinic acid isolated from Rosmarinus officinalis L.

Abstract: The aim of this study was to investigate the antidepressant-like effect of fractions from Rosmarinus officinalis L.: ethyl acetate 1 and 2 (AcOEt1 and 2), hexane (HEX), ethanolic (ET), and essential oil-free (EOF) fractions, as well as essential oil, the isolated compounds carnosol and betulinic acid in the tail suspension test, a predictive test of antidepressant activity. Swiss mice were acutely administered by oral route (p.o.) with fractions, essential oil or isolated compounds, 60 min before the tail susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 25 publications
2
56
0
2
Order By: Relevance
“…The majorities of these studies involved two tests that are used to model antidepressant like effects in mice-the Tail Suspension Test (TST) and Forced Swimming Test (FST). The administration of rosemary continuously decreased the immobility time of mice in both the TST and the FST, indicating an antidepressantlike effect [31][32][33][34]. Rosemary's antidepressant potential was further bolstered when it was found to decrease exploratory and anhedonic-like behavior in bulbectomized mice [35].…”
Section: Antidepressant Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…The majorities of these studies involved two tests that are used to model antidepressant like effects in mice-the Tail Suspension Test (TST) and Forced Swimming Test (FST). The administration of rosemary continuously decreased the immobility time of mice in both the TST and the FST, indicating an antidepressantlike effect [31][32][33][34]. Rosemary's antidepressant potential was further bolstered when it was found to decrease exploratory and anhedonic-like behavior in bulbectomized mice [35].…”
Section: Antidepressant Activitymentioning
confidence: 98%
“…Rosemary has also been found to increase the concentration of neurotransmitters in the brains of mice [33]. Several compounds in rosemary extract and essential oil are responsible for its antidepressant activity, including carnosol, betulinic acid, ursolic acid, and polyphenols [31,33,34].…”
Section: Antidepressant Activitymentioning
confidence: 99%
“…It is well known for its use as a spice for the flavoring of foods, but it is gaining interest for its diverse pharmachological properties (Machado et al, 2013). Leaves of R. officinalis L. have antioxidant, antiinflammatory, antidiabetic, hepatoprotective and antibacterial activities (Ahmed and Abdella, 2010;Altinier et al, 2007;Bakirel et al, 2008;Gutierrez et al, 2010;Del Campo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Daniele et al investigated the antidepressant effect of rosemary essential oil and demonstrated that 1, 8-cineol, found in rosemary essential oil, had antidepressant effect (Machado et al, 2013). Regarding such findings, we can argue that the antidepressant effects of M. pulegium essential oil is due to its main compounds, thymol, carvacrol, and 1, 8-cineol.…”
Section: Discussionmentioning
confidence: 95%